INTEGRATIVE CURRICULUM DEVELOPMENT BASED ON HIGHER ORDER THINKING SKILLS (HOTS) IN PRIMARY EDUCATION - Fuad Hasan (Indonesian Journal of Education and Youth Development, 2025)
This study examines the development of an integrative curriculum and its role in embedding Higher Order Thinking Skills (HOTS) in primary education. Through a systematic literature review, this research finds that an integrative curriculum facilitates holistic learning by connecting various subjects to real-world contexts. Effective pedagogical strategies, such as project-based learning, inquiry-based learning, and contextualized problem-solving, are proven to enhance students' cognitive abilities, including critical thinking, creativity, and problem-solving. Nevertheless, implementation faces challenges, such as a lack of teacher readiness, resource limitations, and policy alignment issues. An integrative curriculum focused on HOTS is crucial for preparing students to be lifelong learners and global citizens..